COMPUTER SUPPORTED COLLABORATIVE LEARNING IN THE TEACHING WRITING - Husni Mubarok (Universitas Islam Nahdlatul Ulama Jepara, 2014)
ABSTRACTThis paper seeks to investigate the effectiveness of computer supported collaborative learning in teaching writing. The discussion is begun with the use of computer supported collaborative learning, the nature of collaborative learning, and will be ended by discussing overviews of writing in general. The main focus of this discussion is the effectiveness of CSCL in teaching writing. In fact, students have low motivation and participation in writing. This is caused by the traditional method that is used by teacher in classroom. By presenting collaborative learning, students will motivate to write. The problem statement above will be analyzed in the term of how is CSCL able to support and enhance students?? language development especially in writing skill. The conclusion is drawn in the form of applying CSCL in teaching writing and teacher role in the classroom.Keywords: Computer supported collaborative learning, collaborative learning, and teaching writingABSTRAKTulisan ini dimaksudkan untuk mengetahui efektivitas komputer didukung pembelajaran kolaboratif dalam pengajaran menulis. Diskusi dimulai dengan penggunaan komputer didukung pembelajaran kolaboratif, sifat pembelajaran kolaboratif, dan akan diakhiri dengan membahas ikhtisar penulisan secara umum. Fokus utama dari diskusi ini adalah efektivitas CSCL dalam pengajaran menulis. Bahkan, siswa memiliki motivasi yang rendah dan partisipasi secara tertulis. Hal ini disebabkan oleh metode tradisional yang digunakan oleh guru di kelas. Dengan menghadirkan pembelajaran kolaboratif, siswa akan memotivasi untuk menulis. Pernyataan masalah di atas akan dianalisis dalam jangka bagaimana CSCL mampu mendukung dan meningkatkan perkembangan bahasa siswa terutama dalam keterampilan menulis. Kesimpulan itu diambil dalam bentuk penerapan CSCL dalam mengajar menulis dan peran guru di kelas.Kata Kunci: Pembelajaran kolaborasi yang didukung dengan komputer, pembelajaran kolaboratif, dan pengajaran menulis